The enlightening work of Metropolitan Pavle Nenadović: the Orthodoxos omologia catechism - Zdravinac, Stefan (Poznańskie Studia Slawistyczne, 2024)
The paper deals with Metropolitan Pavle Nenadović’s booklet Orthodoxos omologia. Special attention is paid to the templates employed in its compilation. In the first part of the paper, Nenadović’s educational work is described in the context of the dominant Enlightenment ideas of the 18th century. The second part of the paper critically examines available sources and testimonies, challenging and reassessing modern hypotheses concerning the templates of Orthodoxos omologia. In conclusion, possible templates of Nenadović’s booklet are offered.